ASSESSING THE IMPACTS OF FLOOD ON THE COMMUNITIES IN DUTSIN-MA LOCAL GOVERNMENT AREA, KATSINA STATE, NIGERIA - Hassan, Abdulhakim Wagini; Ahmed, Abdulrazak; Halliru, Yunusa; Zakari, Ahmad Yahya; Jallo, Ibrahim Umar; Abdulkadir, Jabir; Umar, Abdulmumin Sulaiman (FUDMA JOURNAL OF SCIENCES, 2023)
Floods is one of the most disturbing environmental hazards in Dutsin Ma Local Government Area of Katsina State, Nigeria. The resulting effect is on property loss, economy and the environment. On this basis, this research was carried out to evaluate flood risk areas in Dutsin-ma local government area of Katsina State. a questionnaire survey gathered information regarding flood in the research area. geospatial approaches were used to obtain Satellite imagery of 2020 from United States Geological Survey (USGS) Google Earth platform. Multi Criteria Evaluation approach was used to develop flood risk-vulnerability map for the Dutsin-Ma. Findings from this study shows that 19% of the respondents believed that relocating people to higher grounds is the best way to mitigate the impact of flood, about 22.8% of the respondents believed that construction and maintenance of new drainages is a good option. Result for vulnerability assessment shows that Makera South, Makera North, Garhi East, Garhi West, Sakarya, Kitibawa, Gandi and Makwanta are identified as very high-risk areas. Other high-risk areas include Gidan Gamawa, Garin Mallam, Koranwaya, Wawaye, Zaki, Dage, Taka, Korafawa, Unguwan Nassarawa, Gago, Mawashi and Karki. The study recommended that Distribution of adequate relief materials and public enlightenment would assist to reduce the impact of in the study area. Result of this study can be beneficial to relevant professional bodies and agencies such as town planners, land use land cover planners, emergency, and contingency planners and the general public for control and management of flood.